New troodontid theropod specimen from Inner Mongolia, China clarifies phylogenetic relationships of later‐diverging small‐bodied troodontids and paravian body size evolution. (23rd July 2021) - Wang, Shuo; Zhang, Qiyue; Tan, Qingwei; Jiangzuo, Qigao; Zhang, Huitao; Tan, Lin
Abstract: A new troodontid (LH PV39) recovered from the Upper Cretaceous Wulansuhai Formation, Inner Mongolia, China, is described, highlighting the dorsoventrally compressed sacral centra. The completely fused neurocentral junctions indicate that LH PV39 had reached adulthood at the time of death, but its size is nevertheless 20% smaller than that of the sympatric Philovenator, demonstrating that it is the second small‐bodied troodontid recovered from the Wulansuhai Formation. Phylogenetic analyses scoring LH PV39 using different strategies and performed with different algorithms unambiguously recovered it as a troodontid. While the parsimony‐based analysis scoring LH PV39 as an independent OTU with all of its available characteristics included recovered it as a basal troodontid, the Bayesian analysis suggests a closer relationship of LH PV39 to Almas and an unnamed troodontid from Ukhaa Tolgod, Mongolia (MPC‐D100/1126+D100/3500). Body size analysis confirmed a single trend of gigantism throughout the evolution of troodontids, and suggests that the Late Cretaceous troodontids evolved in two directions: (i) several size‐independent characteristics evolved while retaining the small sizes that are typical of the Early Cretaceous relatives, resulting in the Late Cretaceous small‐bodied troodontids; and (ii) size‐dependent characteristics (e.g., the elongation of the rostrum) evolved accompanying the size increase, resulting in large‐bodied derived troodontids. The mosaic features of the Late Cretaceous small‐bodied troodontids place them intermediate between their Early Cretaceous basal relatives and the Late Cretaceous large‐bodied taxa in a well‐resolved phylogeny, which is crucial for understanding the size and morphological evolution of troodontids.